THE ACTIVITY OF UKRAINIANS IN THE VIENNESE PARLIAMENT AT THE END OF THE 19TH CENTURY (BASED ON MATERIALS FROM THE NEWSPAPER «RUSLAN») - ZULYAK, Ivan; PRYIDUN, Stepan (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2025)
This article examines the political activity of Ukrainian deputies in the Viennese Parliament at the end of the 19th century based on materials from the newspaper «Ruslan». Key aspects of their parliamentary engagement are analyzed, including participation in legislative initiatives, the struggle for the expansion of rights for the Ukrainian population of Galicia, and resistance to political and socio-economic challenges. Particular attention is given to issues related to the electoral process, manifestations of administrative pressure, and repressive measures taken by the authorities against Ukrainian deputies and their supporters. The study is based on publications from «Ruslan», which reflected political rhetoric, parliamentary debates, and assessments of the activities of Ukrainian parliamentarians. The main directions of their work in parliament and their influence on the formation of national-political discourse are identified.